Role of chemokine receptors CXCR4 and CXCR7 for platelet function. (3rd August 2015) - Chatterjee, Madhumita; Rath, Dominik; Gawaz, Meinrad
Abstract : Platelet-derived SDF-1α (stromal cell derived factor-α) mediates inflammation, immune defence and repair mechanisms at site of tissue injury. This review summarizes the relative expression of CXC chemokine receptor 4 (CXCR4) and CXCR7 in platelets, their dynamic trafficking in presence of ligands like chemokine C-X-C-motif ligand 11 (CXCL11), CXCL12 and MIF (macrophage migration inhibitory factor); how these receptors differentially mediate the functional and survival response to the chemokines CXCL11, CXCL12 and MIF. We further elaborate and emphasize the prognostic significance of platelet surface expression of CXCR4–CXCR7 in the context of coronary artery disease (CAD). SDF-1α/CXCL12, CXCL11, MIF effects mediated through CXCR4 and CXCR7 may play a regulatory role at the site of vascular and tissue inflammation, immune defence and repair where activated platelets reach as forerunners and function as critical players.